The Zebrafish Breathes New Life into the Study of Tuberculosis - Myllymäki, Henna; Bäuerlein, Carina A.; Rämet, Mika (Frontiers in Immunology, 2016)
Tuberculosis (TB) is a global health emergency. Up to one third of the world’s population is infected with Mycobacterium tuberculosis, and the pathogen continues to kill almost two million people annually. Currently, the means for preventing, diagnosing, and treating TB are unsatisfactory. One of the main reasons for the poor progress in TB research has been a lack of good animal models to study the latency, dormancy and reactivation of the disease. Although sophisticated in vitro and in silico methods suitable for TB research are constantly being developed, they cannot reproduce the complete vertebrate immune system and its interplay with pathogens and vaccines. However, the zebrafish has recently emerged as a useful alternative to more traditional models, such as mice, rabbits, guinea pigs, and non-human primates, for studying the complex pathophysiology of a mycobacterial infection. The model is based on the similarity between Mycobacterium marinum – a natural fish pathogen – and Mycobacterium tuberculosis. In both zebrafish larvae and adult fish, an infection with M. marinum leads to the formation of macrophage aggregates and granulomas, which resemble the M. tuberculosis infections in humans. In this review we will summarize the current status of the zebrafish model in TB research and highlight the advantages of using zebrafish to dissect mycobacterial virulence strategies as well as the host immune responses elicited against them. In addition, we will discuss the possibilities of using the adult zebrafish model for studying latency, dormancy, and reactivation in a mycobacterial infection.